Analisys of lead (Pb) Heavy Metal Content in Climbing Perch Fish (Anabas testudineus) Derived from Rawa Taliwang Lake, West Sumbawa Regency 2021 - Lili Mantika Shoalichin; Khairuddin Khairuddin; M. Yamin (Jurnal Biologi Tropis, 2022)
Rawa Taliwang Lake as an Nature Park in West Sumbawa Regency have an economic value for the fishermens and fish traders from Climbing Perch fish (Anabas testudinesu). Consuming Heavy metals content in climbing perch fish will be damaged human body. This research aims to analysis of lead (Pb) heavy metal content in climbing perch fish (Anabas testudineus) derived from Rawa Taliwang Lake, West Sumbawa Regency 2021. This research was conducted for two months, starting from September - October 2021. Sampling was carried out by purposive sampling method at 2 research stations. Fish samples were taken are 2 fishes from each station using traditional rattan fish trap. The fish species taken were climbing perch fish. The research sample was then analyzed in the West Nusa Tenggara Health, Testing and Calibration Laboratory. The data analysis was carried out by taking muscle tissue from headsnake fish and then analyzing the content of heavy metal in the from lead using AAS (Atomic Absorbtion Spectrophotometry). The measurement result showed that heavy metal content of lead in climbing perch fish from Rawa Taliwang Lake 0,1 mg/kg (ppm) or still under the maximum standard  by Food and Drug Supervisory Agency (BPOM) No.5 of 2018 concerning the Maximum Limit of Heavy Metal Contamination in Processed Food which is 0,2 mg/kg.